Neuroinmunological response against mump virus - Castillo-González, William; Lumpuy-Castillo, Jairo; Rodríguez-Pérez, José Alejandro; Pérez-del-Vallín, Vanessa; Mirabal-Viel, Alejandro; Meijides-Mejías, Christian; Dorta-Contreras, Alberto Juan (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: Meningoencephalitis is produced by paramixoviridae like mump virus among others. The MMR vaccine are been used for many years in Cuba with a complete coverage that allowed the post-mump meningoencephalitis eradication, but there are some isolate cases reported. Objective: determinate the specific response of IgG mump antibodies in pediatric patient with acute virus meningoencephalitis. Material and Method: A retrospective study was done in 2018. Blood and cerebrospinal fluid from MMR vaccinated pediatric patients suffering from acute virus meningoencephalitis were employed. Anti-mump specific antibody index to identify the immunological response was performed in patients by ELISA. Blood and the cerebrospinal fluid come from the Central Laboratory of Cerebrospinal Fluid collection. Results: All the patients presented intratecal specific response. A significant decrease of anti-mump antibody index according to age and response time were observed. Conclusions: The shortening of response time of anti-mump specific IgG antibody in relation with age of the vaccinated patient were observed. It could happened because of the less immunogenicity of the mump strain used in the vaccine, the vaccine quality, the cold chain violation or the need to a second vaccine reactivation.